PERSPEKTIF SOSIOLOGI PENGETAHUAN BARU TENTANG COVID-19 UNTUK ILMU PEKERJAAN SOSIAL: PEMIKIRAN AWAL - Zaka Lawang, Robert Markus (Jurnal Insani, 2022)
In the analysis of sociology of knowledge, the capacity of poor families during 2 year period of Covid-19 pandemic was resulted from social construction made by individual in her or his own way. The social construction around the Covid-19 issues, came into being as a new reality as part of our lives. Every body is confronted with a choice to accept a number of new knowledge dealing with Covid-19, and take action accordingly. The new knowledges were formal in character such as health standards of behavior, limitations of societal activities. Besides, there were also informal knowledges on traditional medicines for prevention and medication as well, which were believed to be of efficacy. If in conventional sociology of knowledge, culture is excluded from the core, in the new sociology of knowledge however, cultured is defined as formal knowledge which is under study of anthropology and informal knowledge used by people in everyday life. Theoretical and practical reflections taken from this knowledge development, are the needs to revise method of social interventions by using knowledge used in everyday life. Local knowledge is already known widely to the be used for program development and its implementation.